2019
DOI: 10.1021/acsomega.9b00205
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Cell-Free Optical Biosensor for Detection of a Broad Range of Mercury Contaminants in Water: A Plasmid DNA-Based Approach

Abstract: Mercury (Hg) is one of the main water contaminants worldwide. In this study, we have developed both whole-cell and cell-free biosensors to detect Hg. Genetically modified plasmids containing the merR gene were used to design biosensors. Firefly luciferase (LucFF) and emerald green fluorescent protein (EmGFP) genes were separately introduced as a reporter. Both constructs showed a detection limit of 1 ppb (Hg) in Escherichia coli and the cell-free system. We found that higher concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…With the continuous improvement of the industrial level and the continuous utilization of pure water resources, the detection of water pollution by heavy metals has become an increasingly concerning global issue. , As a kind of a heavy metal pollutant, mercury ions (Hg 2+ ) have a great threat to living things especially to human beings. Even small amounts of Hg 2+ in water can cause irreversible damage to the human body, including headaches, low-grade fevers, adrenaline surges, sleep disorders, etc. Therefore, it is very important for people to quickly detect Hg 2+ in living water. , There are many common methods for Hg 2+ detection, such as fluorescence spectrometry, atomic absorption spectrometry, etc. Stobiecka et al have reported the competing fluorescence methods for Hg­(II) detection. , However, these methods still have the disadvantages of long detection time, complex instrument, and high cost. Therefore, it is very important to establish a rapid and effective method to detect Hg 2+ .…”
mentioning
confidence: 99%
“…With the continuous improvement of the industrial level and the continuous utilization of pure water resources, the detection of water pollution by heavy metals has become an increasingly concerning global issue. , As a kind of a heavy metal pollutant, mercury ions (Hg 2+ ) have a great threat to living things especially to human beings. Even small amounts of Hg 2+ in water can cause irreversible damage to the human body, including headaches, low-grade fevers, adrenaline surges, sleep disorders, etc. Therefore, it is very important for people to quickly detect Hg 2+ in living water. , There are many common methods for Hg 2+ detection, such as fluorescence spectrometry, atomic absorption spectrometry, etc. Stobiecka et al have reported the competing fluorescence methods for Hg­(II) detection. , However, these methods still have the disadvantages of long detection time, complex instrument, and high cost. Therefore, it is very important to establish a rapid and effective method to detect Hg 2+ .…”
mentioning
confidence: 99%
“…Looking ahead toward sensor deployment, this work establishes that encapsulation can protect cell-free sensors from degradative sample components while allowing analyte detection in real-world samples. While cell-free sensors have been previously used for the detection of environmental molecules of interest (19), encapsulation of these systems may ultimately diversify the contexts within which cell-free sensors can operate.…”
Section: Discussionmentioning
confidence: 99%
“…Cell-free systems have emerged as a powerful technology to detect a wide variety of molecular signals, including chemical contaminants relevant to the environment and human health (19) and markers of disease and infection (1017). By reconstituting purified cellular machinery in vitro , these systems enable use of natural microbial sensing mechanisms in a low-cost, distributable, and easily tunable platform.…”
Section: Introductionmentioning
confidence: 99%
“…For example, cell-free compatible gene networks can be transcription-based such that the presence of a small molecule induces reporter gene expression, through binding to, and activation or repression of, a transcriptional regulator. These types of transcriptional gene circuits have been used to develop cell-free biosensors for detecting heavy metals (Gräwe et al, 2019;Gupta et al, 2019), a date-rape drug (Gräwe et al, 2019), metabolites (Voyvodic et al, 2019) and quorum sensing molecules from Pseudomonas aeruginosa-infected respiratory samples (Wen et al, 2017). Small molecules can also regulate transcription by binding to endogenous or engineered RNA aptamer-regions within 5 untranslated (UTR) mRNA regions -termed riboswitches.…”
Section: Cell-free Synthetic Biology Enabled Smart Materialsmentioning
confidence: 99%